Multimodal practices of empathy and fear in polish refugee discourse : analysis of magazine covers - Czachur, Waldemar; Opiłowski, Roman; Smykała, Marta (Penerbit Universiti Kebangsaan Malaysia, 2022)
The work is anchored in the paradigm of media linguistics and discourse linguistics, which draw inspiration from cognitive research on language use in the media, semiotic studies, and culture studies. This article is of an empirical nature, as it presents the results of an analysis of selected specific opinion magazine covers. Basing on the selected covers, it aims to characterize the multimodal practices of empathy and fear used in the migration discourse in Poland during the years 2015-2017. This will provide insight into the ways collective knowledge formations are activated by different actors in different media in order to evoke an empathetic attitude or an attitude of fear towards refugees. The analytical corpus consists of 36 covers from ten weekly magazines with high sales rates in Poland. We use the model of multimodal text analysis and the main focus of our analysis is to show the essence of multimodal practices, which, based on specific topoi, activated individually or in combination with others, intend to evoke an attitude of empathy or fear in the recipient. In the case of multimodal practices of empathy and fear, the process of multimodal integration should be considered important as it played the role of a keystone between the verbal and visual layers, and these were the carriers of specific topoi. Multimodal integration determines the process of topoi overlapping, and thus conditions the process of creating specific meanings, which, as previously mentioned, are of persuasive character. Both codes explain each other and specify and illustrate each other by implementing the elaboration pattern.